Control Application of Microwave Technology to Enhance Fatigue Life and Optimize Life-Cycle Cost of Urban Asphalt Pavements - Nguyễn, Phan Anh; Cao, Thị Hồng Hạnh (Journal of Transportation Science and Technology, 2026)
This study evaluates the potential of microwave-assisted self-healing for asphalt concrete on heavy-duty urban roads through calibrated simulation under the conditions of Nguyen Truong To Street (Hai Phong). Performance indices HI, HL, MR and FER are employed to determine the composite fatigue life extension index (FLE). Results indicate that conventional asphalt achieves limited recovery (HI 20–30%, FER ≈35%, FLE ≈1.0). With 25% carbon fiber powder, the FLE rises to about 2.61, while using 80% steel slag yields an FLE of approximately 2.93, suggesting the potential to extend maintenance cycles to 21–26 years and significantly reduce life-cycle costs. These outcomes reflect the predictive trend of fatigue improvement when microwave heating is applied under heavy urban traffic conditions